Hak Asasi Manusia Dalam Konstitusi Indonesia: Implementasi Dan Tantangan - Raisa Qolbina Ibrizzahra; Dzikri Maula Salam; Tabhita Prima Isnaeni; Putri Sahara Herlina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Human rights are the rights of every person, regardless of religion, race, ethnic origin, gender, sexual orientation, or social class. These rights are derived from human dignity created by God Almighty. The state, law, government and society must respect, support and protect human rights. The constitution is a civil agreement or consensus of the people that has provisions to control and guide state leaders in carrying out their duties and responsibilities, so that national leaders have a compass to know the direction and goals agreed upon in the hands of the people and the constitution. This research uses descriptive research, which is a research process to determine the value of one or more variables concerned. The results of this research show that there are many human rights challenges in Indonesia, such as discrimination is still a problem that affects the lives of many people. Discrimination can occur in various areas, such as education, healthcare, and employment. Among the many groups that face discrimination in Indonesia are ethnic minority groups and women.